Flux through mitochondrial redox circuits linked to nicotinamide nucleotide transhydrogenase generates counterbalance changes in energy expenditure - Smith, Cody D. (J Biol Chem, 2020)
Compensatory changes in energy expenditure occur in response to positive and negative energy balance, but the underlying mechanism remains unclear. Under low energy demand, the mitochondrial electron transport system is particularly sensitive to added energy supply (i.e. reductive stress), which exponentially increases the rate of H(2)O(2) (JH(2)O(2)) production. H(2)O(2) is reduced to H(2)O by electrons supplied by NADPH. NADP(+) is reduced back to NADPH by activation of mitochondrial membrane potential–dependent nicotinamide nucleotide transhydrogenase (NNT). The coupling of reductive stress-induced JH(2)O(2) production to NNT-linked redox buffering circuits provides a potential means of integrating energy balance with energy expenditure. To test this hypothesis, energy supply was manipulated by varying flux rate through β-oxidation in muscle mitochondria minus/plus pharmacological or genetic inhibition of redox buffering circuits. Here we show during both non-ADP– and low-ADP–stimulated respiration that accelerating flux through β-oxidation generates a corresponding increase in mitochondrial JH(2)O(2) production, that the majority (∼70–80%) of H(2)O(2) produced is reduced to H(2)O by electrons drawn from redox buffering circuits supplied by NADPH, and that the rate of electron flux through redox buffering circuits is directly linked to changes in oxygen consumption mediated by NNT. These findings provide evidence that redox reactions within β-oxidation and the electron transport system serve as a barometer of substrate flux relative to demand, continuously adjusting JH(2)O(2) production and, in turn, the rate at which energy is expended via NNT-mediated proton conductance. This variable flux through redox circuits provides a potential compensatory mechanism for fine-tuning energy expenditure to energy balance in real time.